2017
DOI: 10.18869/acadpub.jafm.73.239.26702
|View full text |Cite
|
Sign up to set email alerts
|

A New Formulation for Prediction of Permeability of Nano Porous Structures using Lattice Botzmann Method

Abstract: The standard lattice Boltzmann equation, LBE, is inadequate for simulating gas flows in nano scale flows with Knudsen numbers higher than 0.1. In the present study, rarefied gas flow in nano porous structures is simulated using the modified Lattice Boltzmann Method, LBM, which is able to cover wide range of flow regimes. The present study, reports the effects of the Knudsen number and porosity on the flow rate and permeability in slip and transitional flow regimes. For the first time, the Knudsen's minimum eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Generally, the porous media is used in the channels to increase the rate of HT. Flow through a sudden expansion channel is a well-known phenomenon [Mostafavi et al (2017)]. Many authors [Mostafavi et al (2017); Menouer et al (2019)], experimentally and numerically, have shown that the increase in Re causes the existence of two or more flow separation zones at the lower and upper corner walls, which causes a substantial heat loss [Galuppo et al (2017)].…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the porous media is used in the channels to increase the rate of HT. Flow through a sudden expansion channel is a well-known phenomenon [Mostafavi et al (2017)]. Many authors [Mostafavi et al (2017); Menouer et al (2019)], experimentally and numerically, have shown that the increase in Re causes the existence of two or more flow separation zones at the lower and upper corner walls, which causes a substantial heat loss [Galuppo et al (2017)].…”
Section: Nomenclaturementioning
confidence: 99%
“…Flow through a sudden expansion channel is a well-known phenomenon [Mostafavi et al (2017)]. Many authors [Mostafavi et al (2017); Menouer et al (2019)], experimentally and numerically, have shown that the increase in Re causes the existence of two or more flow separation zones at the lower and upper corner walls, which causes a substantial heat loss [Galuppo et al (2017)]. Hilo et al (2020) studied different properties of the hydrothermal phenomena of flow over a suddenly expanded channel.…”
Section: Nomenclaturementioning
confidence: 99%
“…All permeability models given so far apply to continuum flow regime. Mostafavi et al (2017) proposed relation given in eq. ( 9), which also depends on Kn, for the porosity calculation of the porous structure formed by in-line arrangement of square particles.…”
Section: Introductionmentioning
confidence: 99%